Work-Induced Stress and Job Performance of Academic Staff in The University of Ilorin, Nigeria - Babatunde Samson Adebayo (Indonesian Journal of Multidiciplinary Research, 2022)
The term job stress could be viewed as a group of external harmful factors in the work environment, which may be psychological, physical, or social. This study examined work-induced stress and job performance of academic staff in the University of Ilorin, Nigeria. A descriptive research design of survey type was adopted for the study. The population comprised all academic staff in the University of Ilorin. Systematic sampling technique was used to select academic staff in faculties of Education, Physical sciences, and Agriculture. 115 respondents (30% of the population) were selected through a proportionate sampling technique. The instrument was a structured questionnaire.  A reliability coefficient of 0.76 was obtained through the test re-test method. The findings revealed significant relationships between role ambiguity, extended hours of work, working conditions, and job performance of academic staff. However, there was no significant relationship between excess workload and job performance of academic staff. Based on the findings, the university management should lessen the burdens of lecturers by reducing additional responsibilities which in turn could lead to increased job performance. Furthermore, the management should provide infrastructural facilities such as electricity and befitting offices for lecturers while classrooms should be adequately equipped using the NUC benchmark.